Intranasal delivery: An attractive route for the administration of nucleic acid based therapeutics for CNS disorders - Shah, Pranav; Lalan, Manisha; Barve, Kalyani (Frontiers in Pharmacology, 2022)
The etiologies of several cardiovascular, inflammatory, neurological, hereditary disorders, cancer, and infectious diseases have implicated changes in the genetic set up or genetic mutations as the root cause. Nucleic acid based therapeutics (NBTs) is a new class of biologics that are known to regulate gene expression at the transcriptional and post-transcriptional level. The NBTs include oligonucleotides, nucleosides, antisense RNA, small interfering RNAs, micro RNA etc. In recent times, this new category of biologics has found enormous potential in the management of cardiovascular, inflammatory, neurological disorders, cancer, infectious diseases and organ transplantation. However, the delivery of NBTs is highly challenging in terms of target specificity (intracellular delivery), mononuclear phagocyte system uptake, stability and biodistribution. Additionally, management of the above mentioned disorders require regular and intrusive therapy making non-invasive routes preferable in comparison to invasive routes like parenteral. The nasal route is garnering focus in delivery of NBTs to the brain in the management of several CNS disorders due to the associated merits such as non-invasiveness, possibility of chronic delivery, improved patient compliance, avoidance of hepatic and gastrointestinal metabolism as well as ability to bypass the BBB. Hence in recent times, this route has been sought by the reserachers as an alternative to parenteral therapy for the delivery of several NBTs. This review shall focus on an array of NBTs delivered through nasal route, their challenges, applications and opportunities. The novel delivery systems for incorporating NBTs; their targeting strategies shall be critically reviewed. The challenges towards regulatory approvals and commercialization shall also be discussed at large. Comparison of learnings derived from the success and barriers in nasal delivery of NBTs will help in identification of futuristic opportunities for their translation from bench to bedside.